Adaptive Introgression across Semipermeable Species Boundaries between Local Helicoverpa zea and Invasive Helicoverpa armigera Moths. (29th April 2020) - Valencia-Montoya, Wendy A; Elfekih, Samia; North, Henry L; Meier, Joana I; Warren, Ian A; Tay, Wee Tek; Gordon, Karl H J; Specht, Alexandre; Paula-Moraes, Silvana V; Rane, Rahul; Walsh, Tom K; Jiggins, Chris D
Abstract: Hybridization between invasive and native species has raised global concern, given the dramatic increase in species range shifts and pest outbreaks due to anthropogenic dispersal. Nevertheless, secondary contact between sister lineages of local and invasive species provides a natural laboratory to understand the factors that determine introgression and the maintenance or loss of species barriers. Here, we characterize the early evolutionary outcomes following secondary contact between invasive Helicoverpa armigera and native H. zea in Brazil. We carried out whole-genome resequencing of Helicoverpa moths from Brazil in two temporal samples: during the outbreak of H. armigera in 2013 and 2017. There is evidence for a burst of hybridization and widespread introgression from local H. zea into invasive H. armigera coinciding with H. armigera expansion in 2013. However, in H. armigera, the admixture proportion and the length of introgressed blocks were significantly reduced between 2013 and 2017, suggesting selection against admixture. In contrast to the genome-wide pattern, there was striking evidence for adaptive introgression of a single region from the invasive H. armigera into local H. zea, including an insecticide resistance allele that increased in frequency over time. In summary, despite extensive gene flow after secondary contact, the species boundaries are largely maintained except for the single introgressed region containing the insecticide-resistant locus. We document the worst-case scenario for an invasive species, in which there are now two pest species instead of one, and the native species has acquired resistance to pyrethroid insecticides through introgression.